(untitled) (Comprehensive Journal of Science, 2025)
This research addresses occupational injuries and accidents at the Tripoli Oil and Gas Depot during the period 2020–2023, within the framework of a study that aims to highlight the reality of occupational safety and health in the oil sector, which is considered one of the most hazardous industries. The theoretical part covered the definition, objectives, and importance of occupational safety and health, in addition to the causes of accidents, their classifications, and prevention strategies. The practical part included a statistical analysis of the number of recorded injuries during the study years, distributed by month, cause, type of injury, and body location. The results indicated that the year 2020 recorded the highest number of injuries, with contusions and upper limb injuries—particularly to the hands and fingers—being the most common. The study concludes that strengthening preventive systems, providing continuous training, and improving the work environment are essential to reducing the recurrence of such accidents and enhancing occupational safety standards in oil depots.